Validasi Modul Pelatihan Pendampingan Klien pada Pekerja Sosial - Yova Tri Yolanda; Muhana Sofiati Utami (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2017)
Purpose of this research is to validate the module Client Facilitating Training to increase social worker knowledge about stress and skill for facilitating client. Training included psychoeducation about stress and management stress, basic of client facilitating method and communication skill in facilitating the process. Subjects of this research are 12 social workers and divided to experiment and control group. This research using quasi-experiment with no control group design with pretest and posttest sample. Data collected by management stress questionnaire, facilitating scale and field data collected by observer and supervisor. Results indicated that there is a significant difference between experiment and control groups in stress and management stress (Z=-3,017; p<0,05) with the large effect size of 0,87 and Facilitating skill (Z= -1,354; p<0,05) with a large effect size of 0,84. Client Facilitating Training is valid to improve social worker knowledge stress and managing stress and facilitating skill.